The Film Dirty Vote from Roland Barthes' Perspective - Yulianto, Hermawan (IHSA Institute, 2024)
Dirty Vote is a documentary film that will appear ahead of the 2024 General Election. The aim of this study is to understand the descriptive nature of the documentary film Dirty Vote in depth using the concept of Roland Barthes' Semiotics with three aspects, namely denotation, connotation and myth. The data source for this study is watching the documentary film Dirty Vote which was uploaded directly from the YouTube Center for Indonesian Law and Policy Studies. The method used is a qualitative content analysis study which emphasizes discourse analysis. The results of this study found that the documentary film Dirty Vote has relevance to Roland Barthes' concept of semiotics, where in the documentary film Dirty Vote there are explicit words, words, signs or symbols, and implied images and hopes for something that has not happened from several words, signs or symbols and images